Pengembangan Bahan Ajar Fisika Kontekstual Untuk Meningkatkan Penguasaan Konsep Siswa - Widya Oktaviani; Gunawan Gunawan; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to determine the influence of contextual physics teaching materials in an effort to improve the mastery of student concepts. This research is a type of research development (reseach and development). The population is all students of class XI IPA SMA Negeri 2 Mataram 2016/2017 school year amounted to 365 students. The sample was determined by purposive sampling technique so that it was obtained by class XI IPA 2 (38 students) as experimental class and class XI IPA 3 (40 students) as control class. The instrument used to measure conceptual mastery is a multiple-choice test. The results showed that the use of contextual teaching materials influential in improving the mastery of the concept of students.